Contextual Modulation of Binary Decisions in Dyadic Social Interactions - Fehr, Thorsten; Achtziger, Anja (Frontiers in Behavioral Neuroscience, 2021)
The present experimental design allowed binary decisions (i.e., to choose between proactive approaching or withdrawing behaviour). These decisions were made on complex social interaction-scenarios displayed on videos. The videos were taken from a first-person perspective. They were preceded by one sentence each that provided additional information about the context of the displayed scenario. The sentence preceding the video and the video jointly provided a context of emotional valence. That context varied from trial to trial. We observed that provocative and threatening videos produced predominantly fear and anger responses. Fear was associated with withdrawal decisions, while anger led to approach decisions. Negative contextual information increased the probability of approach decisions in aggressive provocative videos, positive contextual information enhanced the chance of approach decisions in socially positive videos. In neutral situations, displayed in videos, the probability of approach behaviour was reduced in case of negative contextual information. Yet, the probability for approach behaviour was increased if positive contextual information preceded neutral videos. Our experimental setup provided a paradigm that can be adapted and accommodated for the examination of future research questions on social decisions in multi-dimensional, complex social situations.